Gait characteristics in women's safety shoes. (November 2017) - Goto, Kanako; Abe, Kaoru
Abstract: Although workers in Japan are required to wear safety footwear, there is concern about occupational accidents that occur when wearing safety shoes. This study aimed to analyze the effect of wearing hardsoled safety shoes on both spatiotemporal gait characteristics and the muscle activity in the lower extremities. Seventeen young women participated in this study. A 5-m gait trial and a surface electromyography trial were conducted while the women walked in either safety shoes or sports shoes. Paired t-tests were performed to analyze the differences in gait characteristics when walking in the two different pairs of shoes. Walking in safety shoes was associated with a significant increase in vastus lateralis, biceps femoris and tibialis anterior activity. This increased muscle activity in the lower extremities is likely compensating for the lower flexibility of the safety shoes. Highlights: Gait characteristics and electromyograms in women's safety shoes were analyzed. Muscle activity related to knee flexion/extension was significantly increased. Activity of lower extremity muscles compensates for shoes with less flexible sole.